Evaluating training cascade mechanism: a methodology and a case study - Rafi, Mohammad (BRAC Research and Evaluation Division (RED), 2019)
Training has increasingly turned into an important NGO tool for rural development in Asia and Africa. Such an use has made it essential to assess the impact of these training sessions. Again a good portion of these sessions are offered through cascade mechanism. There has been a skepticism on the effectiveness of this mechanism. In response to the above need and skepticism the paper assessed the effectiveness of social development training and the caseade mechanisms under the Human Rights and Legal Education program of Bangladesh Rural Advancement Committee. A theoretical framework was developed and used for the assessment. The findings show that the training was effective in producing desired changes and the cascade mechanism was an effective training tool.